Simulation and software for research of ejector operation in variable modes - Дмитро Вікторович Коновалов; Роман Миколайович Радченко; Сергій Георгійович Фордуй; Фелікс Володимирович Царан; Віктор Павлович Халдобін; Артем Вікторович Грич (Радіоелектронні і комп'ютерні системи, 2021)
One of the current directions of development of modern energy-saving and energy-efficient technologies for ship and stationery (including municipal) energy is the use of ejector refrigeration machines, which can be used for air conditioning systems together with an absorption refrigeration machine (cascade cycle) or vapor compressor refrigeration machine as part of cogeneration or trigeneration units. Such circuit solutions can be used together with ensuring the rational organization of work processes in the main elements of the refrigeration machine, in particular in the jet device - ejector, the appropriate design of which, in turn, will further increase the thermal coefficient. Improving the design of the ejector is a rather complex and long process and does not always give positive results. It is primarily because many tests are required on full-scale models. Therefore, computer simulation of the ejector operation at different variable input parameters, considering the geometric characteristics of the flow part and variable mode characteristics during operation is more attractive in terms of finding options for rational (optimal) design. The paper presents the results of software development for modeling hydrodynamic processes in the flowing part of the ejector, considering the variable operating modes of the ejector refrigeration machine. The existing method for calculating the pressure and circulation characteristics of jet devices is used. The developed software complex "RefJet" in the design mode defines the maximum achievable coefficients of ejection of a jet ejector. In the simulation mode - provides determination of the ejection coefficients of the already designed (certain sizes) ejector at variable values of pressure at the inlet and outlet in specific operating conditions, considering its operation at the limit and partial modes. The work of the software package was tested in the development and analysis of circuit solutions of ejector refrigeration machines as part of the heat recovery circuits of three-generation units based on internal combustion engines and gas turbine engines.